Tax Reduction for the Entry of Taxpayers By the Supply Chain Strategies - Hassan Salim Mohsin; Suad Jawad Kadhim; Ahmed Kadhim Sendw (International Journal of Supply Chain Management, 2019)
The research stems from a problem of prevalence of tax evasion phenomenon from taxpayers and its negative and serious impacts resulting therefrom. The results of such negative and serious impacts are represented in a decrease tax revenue proceeds and the damages to the public treasury of the state, as well as the occurrence of evader taxpayers under the law and take the penalties and legal sanctions against them by the tax authority. For the purposes of this research, tax exemption can be perceived as those exemptions granted on the incomes of natural and moral taxpayers. These are determined by a general or private legislative text for the purpose of achieving tax justice, by taking into account the circumstances of the personal, family and family taxpayer, and to prevent double taxation. Such cases may be Temporary, or permanent, or partial exemption for the purpose of achieving the economic, political and social objectives sought by the state. The research aims to highlight the tax exemptions granted to the taxpayers in accordance with the amended Income Tax Law No. (113) for the year 1982 and the applied legislations and laws, show their suitability to basic tax rules, and identify the role of tax exemptions to reduce the tax evasion phenomenon, and thus increase tax revenues. The present study used case study method to prove and establish the result and finding supported by the financial numbers and previous research literature. The paper is concluded by offering some recommendations to the policy makers and other important stakeholders.